High rate capability achieved by reducing the miscibility gap of Na4−xMnV(PO4)3. Issue 21 (9th September 2022) - Tang, Ao; Lin, Weiguang; Xiao, Dongdong; Shang, Chaoqun; Yan, Min; Zhang, Zhanhui; Aifantis, Katerina; Hu, Pu
Abstract : Reducing the grain size to the nanoscale enables fast kinetics and rate capability due to narrowing the miscibility gap of Na4− x MnV(PO4 )3, which effectively suppresses the phase transformation of materials during the electrochemical process. Abstract : NASICON structured Na4 MnV(PO4 )3 has attracted great interest as a promising cathode for sodium-ion batteries due to its high theoretical capacity and working potential. However, it suffers from poor cycling stability and rate capability that originate from multi-phase transformations during sodiation/desodiation. In this work, the effect of synthesis conditions on the structural evolution, the reaction mechanism and the phase evolution of such electrode materials during sodiation/desodiation was investigated. The results indicate that the reaction mechanism depends on the grain size of Na4 MnV(PO4 )3 . Specifically, reducing the grain size allows for an expanded solid solution region, which considerably improves the cycling stability and rate capability. Tuning the grain size can therefore improve the structural stability and kinetics of Na4 MnV(PO4 )3 .